Tuan guru and social change in Lombok, Indonesia. Issue 135 (4th May 2018) - Fahrurrozi,
ABSTRACT: This article discusses the role of tuan guru as Islamic leaders among Sasak society on the island of Lombok. Although there are several traditional criteria for calling someone a tuan guru, there remains debate about which features are most important and which aspects are optional. Tuan guru play various cultural roles in society, including not only educator and guardian of traditional culture but also social mediator. The place of this category of traditional leader has been shifting over the past several decades though, in response to both general trends of modernity and the specific context of Lombok and Indonesia. The article discusses both the direction of the trends (towards loosening the requirements for ascribing the title tuan guru ) and some of the specific factors at play.